Escherichia coli Eyelid Abscess in a Patient with Alcoholic Cirrhosis. (15th September 2015) - Stratton, Matthew; Capitena, Cara; Christensen, Logan; Paciuc-Beja, Miguel
Abstract : Escherichia coli ( E. coli ) is a rare cause of ocular infections and has not yet been reported as a cause of an ocular abscess. We describe the case of a 47-year-old woman with a history of alcoholic cirrhosis who presented with painful left lower eyelid swelling that did not improve with oral antibiotics. The abscess was drained and cultures were positive for E. coli . Patients with cirrhosis are at increased risk for developing E. coli bacterial infections, but to our knowledge this is the first case of an E. coli eyelid abscess reported in the literature.